Translational Medicine in Tissue Regeneration - Rogério Leone Buchaim; Daniela Vieira Buchaim (Open Journal of Biological Sciences - Peertechz Publications, 2017)
Translational medicine basically aims to facilitate the integration of basic research with clinical research, with the aim of transferring the applicability of its benefi ts to the population as a whole [1,2]. According to Lean et al., "It is a process that part of the evidence-based medicine towards sustainable solutions to community health problems" [3]. In addition, translational research generates an increase in the capacity for health research with an interdisciplinary and multidisciplinary approach, forming, training and integrating a new generation of researchers [4].